2022
DOI: 10.1155/2022/5717445
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Identification of Serum Exosome-Derived Biomarkers for Bipolar Disorder

Abstract: Background. Exosomes are extracellular vesicles that play important roles in various physiological and pathological functions. Previous studies have demonstrated that exosome-derived contents are promising biomarkers to inform the pathogenesis and diagnosis of major depressive disorder and schizophrenia. Methods. We used ultraperformance liquid chromatography-tandem mass spectrometry to analyze the differentially expressed metabolites in serum exosomes of patients with bipolar disorder (BD) and evaluated the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 27 publications
1
25
0
1
Order By: Relevance
“…Several bioreactions have been revealed to exhibit great importance during the pathogenesis, including galactose biochemical processing, amino sugar and nucleotide sugar reactions, and the mutual interconversion between pentose and glucuronic acid. 73 This is consistent with a previous study of multi-pathway alterations in BD plasma metabolomics. 97 This has strongly suggested that the dysfunction of glucose metabolism is closely related to the occurrence and deterioration of BD.…”
Section: How Potential Of Metabolomics Of Extracellular Vesicles In C...supporting
confidence: 93%
See 2 more Smart Citations
“…Several bioreactions have been revealed to exhibit great importance during the pathogenesis, including galactose biochemical processing, amino sugar and nucleotide sugar reactions, and the mutual interconversion between pentose and glucuronic acid. 73 This is consistent with a previous study of multi-pathway alterations in BD plasma metabolomics. 97 This has strongly suggested that the dysfunction of glucose metabolism is closely related to the occurrence and deterioration of BD.…”
Section: How Potential Of Metabolomics Of Extracellular Vesicles In C...supporting
confidence: 93%
“…Serum-derived EVs are essential not only for bipolar disorder research, 73 they also provide anti-inflammatory substances and antibiotics to COVID-19 patients, 74 as well as in Alzheimer’s disease. 50 , 75 Due to the complexity of whole blood substances, blood-derived EVs are rarely used.…”
Section: How Potential Of Metabolomics Of Extracellular Vesicles In C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Para a análise desse fator é utilizado o cérebro pós morte e amostras de sangue (Andreazza, et al, 2015). Outro parâmetro que está sendo investigado para o possível diagnóstico de TB, são as desregulações de metabólitos exossomais no início ou desenvolvimento do TB, indicando assim que os metabólitos exossomais sanguíneos são fortes candidatos para informar o diagnóstico de TB (Du, et al, 2022). Diante dos dados expostos acima, o tratamento do TB ainda é considerado um desafio grande, uma vez que é preciso debelar qualquer episódio agudo e evitar que novos ocorram.…”
Section: Resultsunclassified
“…Metabolomics is a discipline to obtain all information of metabolites in a biological sample and would give mechanistic insights into the etiology of DD ( Nedic Erjavec et al, 2018 ; Du et al, 2022 ). For example, nine potential biomarkers involved the depression pathogenesis were identified based on metabolomics analysis by comparing the rats’ serum metabolites of CUMS(chronic unpredictable mild stress) model group and Xiao-Chai-Hu-Tang group ( Xiong et al, 2016 ).…”
Section: Future Perspectivesmentioning
confidence: 99%